Peluang Partisipasi Politik Perempuan di Indonesia Dalam Prespektif Hak Asasi Manusia - Irma Permata Sari; Muhyidin (Universitas Sunan Drajat Lamongan, Indonesia, 2024)
Women's participation in politics is still perceived as representation in political structures at the national and regional levels, which is felt to be inadequate. Even though the quantitative existence of women is even comparable to half of the population both at the national and regional levels. One of the inhibiting factors is the party culture. We can see directly in several political events or general elections that women only have a few seats and voting space. We can conclude that Indonesian people think that men are more competent to be leaders than men. The results of the study show that the position, role and function of women indicates that there is space for participation but women are still not actively involved, which is influenced by internal and external factors, including low levels of education, ancient thinking that considers men more competent than men. Woman. With this paper, the authors hope that there will be equality for men and women in participating in politics so that in the future the Indonesian people choose leaders by looking at their abilities, not from considerations of gender, race, ethnicity and culture, or religion. Because in truth every human being has the right to be treated equally in participating in politics.